Sinusoidal phase modulating interferometer for real-time surface profile measurement - Guotian, He; Helun, Jiang; Xingwen, Tan (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
The optical interferometry for the surface profile measurement is high accuracy, non-contact, and has a wide application in industry and scientific research. In this paper, a sinusoidal phase modulating (SPM) interferometer to realize real-time surface profile measurement is proposed, and its measuring principle is analyzed theoretically. In the SPM interferometer, the interference signal is detected by a high speed image sensor based on a low-speed CCD and a signal processing circuit is used to obtain the phase of each point on the surface. Therefore, the surface profile can be measured real time. The experiments measuring the surface profile of a wedge-shaped optical flat show that the measurement time of the SPM interferometer is less than 10 ms, the repetitive measurement accuracy is 5.2 nm. The experimental results confirm the validity of the SPM interferometer, and the merits of the interferometer is simple structure, high measurement accuracy.
Optica Applicata, Vol. 38, 2008, nr 2, s. 413-420
Keywords: optyka; real-time measurement; surface profile; SPM interferometer